Peranan Kepolisian Dalam Penanggulangan Tindakan Kejahatan Pencurian Dengan Kekerasan (Begal) Di Wilayah Hukum Polsek Percut Sei Tuan - Hartono Hartono; Syafruddin Kalo; M Hamdani; Mahmud Mulyadi (Iuris Studia: Jurnal Kajian Hukum, 2021)
This study aims to determine the role of the police in overcoming violent crimes (begal) in the jurisdiction Sector Police (POLSEK) Percut Sei Tuan Medan. The data used in this study are primary data and secondary data. Primary data were obtained through interviews with several parties related to research topics and secondary data obtained by studying books, magazines and legislation related to the research topic. Next, data obtained were analyzed quantitatively and presented descriptively. The results of this study indicate that tackling violent crimes (begal) in the jurisdiction Police Sector POLICE) Percut Sei Tuan Medan, which is in accordance with Law No. 2 of 2002 contained in Article 5 paragraph 1. Obstacles in overcoming crime the crime of theft with violence at the Sei Tuan Medan Police is a lack of participation from the Community. The community plays an important role in overcoming the crime of theft with violence so that between the community and the police have a relationship with each other